ANALYSIS OF FUNDAMENTAL FACTORS AFFECTING COMPANY VALUE WITH DIVIDEND POLICY AS INTERVENING VARIABLES IN THE COVID-19 PANDEMIC (Study on the Consumer Goods Industry Sector) - Widajatun, Vincentia Wahju (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to look at the condition of companies in the consumer goods industry sector during a pandemic to analyze fundamental factors using the Return On Assets, Debt to Equity Ratio (DER) and Net Profit Margin (NPM) indicators on company value with PBV and PER indicators with dividend policy. as an intervening variable which is proxied by dividend payout ratio. This research was conducted in the consumer goods industry sector with a population of 53 and a sample of 46 companies. The data analysis technique used to discuss the problems in this research is the Structural Equation Model (SEM). The results showed that the influence of Fundamental Factors on Firm Value had a significant effect with the T-Statistic of (3.230 > 1.96). The results of the second study The Effect of Fundamental Factors on Dividend Policy has a significant effect with a T- statistic of (4,659 <1.96). The results of the third study the effect of Dividend Policy on Firm Value has a significant T-statistical effect of (4,629 <1.96).